Inadequate weight gain and factors influencing it among preterm neonates in neonatal intensive care units in the Amhara region, Ethiopia, in 2022 - Semanew, Yaregal; Tesfaye, Eleny; Tesgera, Debrework (Frontiers in Pediatrics, 2024)
Adequate weight gain is crucial for the health and development of preterm neonates admitted to neonatal intensive care units (NICUs). Understanding the factors influencing weight gain in this vulnerable population is essential for improving outcomes. This study aimed to assess the weight gain status and associated factors among preterm neonates admitted to NICUs in specialized hospitals in the Amhara region of Ethiopia.A cross-sectional study design was employed, involving 363 preterm neonates admitted to NICUs in specialized hospitals within the Amhara region. Data were collected using structured questionnaires and Kobo Tool Box. Daily weight measurements were recorded for three consecutive days. Descriptive statistics, logistic regression analysis, and graphical presentations were utilized for data analysis and presentation.The study revealed that a significant proportion (80.8%) of preterm neonates experienced poor weight gain during their NICU stay. Factors significantly associated with poor weight gain were older maternal age, delayed initiation of enteral feeding, lack of kangaroo mother care, and inadequate antenatal care visits.Addressing the identified factors, such as providing adequate support during the antenatal period, promoting timely initiation of enteral feeding, and encouraging kangaroo mother care practices, is crucial for improving weight gain outcomes in preterm neonates.These findings highlight the importance of a comprehensive approach to neonatal care, targeting both maternal and neonatal factors. Policymakers and healthcare providers should prioritize interventions aimed at optimizing weight gain in preterm neonates to improve their overall well-being and long-term outcomes.